2010
DOI: 10.1016/j.taap.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane protects Microcystin-LR-induced toxicity through activation of the Nrf2-mediated defensive response

Abstract: Microcystins (MCs), a cyclic heptapeptide hepatotoxins, are mainly produced by the bloom-forming cyanobacerium Microcystis, which has become an environmental hazard worldwide. Long term consumption of MC-contaminated water may induce liver damage, liver cancer, and even human death. Therefore, in addition to removal of MCs in drinking water, novel strategies that prevent health damages are urgently needed. Sulforaphane (SFN), a natural-occurring isothiocyanate from cruciferous vegetables, has been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
3
33
0
1
Order By: Relevance
“…These results thus suggest the involvement of ROS in SFN induced increase in MICA/MICB expression. This is in agreement with many reports which confirm that the ROS mediated signaling pathway is the major mediator of SFN including induction of Antioxidant Response Element (ARE) genes as well as mediating mitotic arrest or apoptosis [24,39,40]. Increase in the expression of cyclin B1 and the phosphorylation of Cdk1 on treatment with sulforaphane was also found to be reversed by NAC pretreatment confirming that ROS is the major player in mediating the effects of SFN [41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results thus suggest the involvement of ROS in SFN induced increase in MICA/MICB expression. This is in agreement with many reports which confirm that the ROS mediated signaling pathway is the major mediator of SFN including induction of Antioxidant Response Element (ARE) genes as well as mediating mitotic arrest or apoptosis [24,39,40]. Increase in the expression of cyclin B1 and the phosphorylation of Cdk1 on treatment with sulforaphane was also found to be reversed by NAC pretreatment confirming that ROS is the major player in mediating the effects of SFN [41].…”
Section: Discussionsupporting
confidence: 92%
“…They include (a) inhibition of phase 1 metabolism enzymes that convert procarcinogens to carcinogens and induction of phase 2 metabolism enzymes that promote excretion of carcinogens [22], (b) induction of apoptosis and cell cycle arrest associated with regulation of many molecules including Bcl-2 family proteins, caspases, p21, cyclins, and cyclindependent kinases [5], (c) suppression of angiogenesis and metastasis by downregulating vascular endothelial growth factor, HIF-1α, matrix metalloproteinase-2 and matrix metalloproteinase-9 [5], (d) induction of cytoprotective proteins via the Nrf2 pathway and reduction of oxidative stress [23,24] and (e) inhibition of histone deacetylases [25].…”
Section: Discussionmentioning
confidence: 99%
“…These observations appear to be in conflict with a number of publications that suggest that protective effects of H 2 S are mediated by upregulating Nrf2-dependent signaling via sulfhydration (7). However, it has been reported that expression of Nrf2 depends on stress levels; low oxidative stress could increase the expression of Nrf2, whereas high oxidative stress might decrease Nrf2 and Nrf2-dependent antioxidant genes (6,31). It was recently reported that hydrogen peroxide activates Nrf2 by inactivation of Kelch-like ECH-associated protein 1 (Keap1) via formation of an intramolecular disulfide bridge releasing inhibition of Keap1 on Nrf2 (7).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian tissues, H 2 S is generated by cystathionine b-synthase (CBS), cystathionine c-lyase (CSE) (22), and 3-mercaptopyruvate sulfurtransferase (3MST) (21). On the other hand, H 2 S is serially oxidized to persulfide, sulfite (SO 3 2 -), thiosulfate (S 2 O 3 2 -), and sulfate (SO 4 2 -) in reactions catalyzed by several enzymes including sulfide:quinone oxidoreductase (SQR), sulfur dioxygenase ethylmalonic encephalopathy 1 (ETHE1), sulfurtransferase rhodanese, and sulfite oxidase (SUOX) (6,8). H 2 S can exert a host of biological effects on various targets ranging from cytotoxicity to cytoprotection.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic cyanobacterial blooms in freshwater rivers, lakes, reservoirs, and recreational waters have increasingly become a nuisance (Cohen, 1989;Chorus and Bartram, 1999;Carmichael, 2001;Paerl et al, 2001;Vasconcelos and Pereira, 2001;Huisman et al, 2005;Liu et al, 2006;Vareli et al, 2009;Ye et al, 2009;Gan et al, 2010). It is well known that many species of cyanobacteria are able to produce microcystins (MCs) (van Apeldoorn et al, 2007), which can accumulate in the food chain (Xie et al, 2005;Chen et al, 2009a) and negatively affect aquatic organisms, animals, and human beings due to their potent hepatotoxicity and probable tumor promoters (Andersen et al, 1993;Carmichael and Falconer, 1993;Chorus and Bartram, 1999;Matsunaga et al, 1999;Carmichael et al, 2001;Zimba et al, 2001;Chen et al, 2002Chen et al, , 2009bQiu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%